HUBUNGAN MOBILISASI DINI POST SECTIO CAESAREA TERHADAP PENYEMBUHAN LUKA BEKAS OPERASI - Thirtinia, Deby; Yulinda Aswan; Mastiur Napitupulu; Dina Mariana Manurung (Jurnal Kesehatan Ilmiah Aufa Royhan, 2025)
Wound healing was a complex process which involves regeneration network formation of epithelial and connective scar tissue. Early mobilization important for know how the wound healing process was especially in mothers who experienced post sectio caesaria. The purpose of this research was to know association of early mobilization post sectio caesarea on wound healing of sectio caesarea at Tk IV 01.07.03 General Hospital In Padangsidimpuan. The Research methods used was Quantitative, Prospective Cohort Study Design with accidental sampling approach. The population studied was all post sectio caesarean women in July-August. Sampling used total sampling as many as 31 respondents. The Data analyzed used the chi-square test with a confidence level of 95% α = 0.05, after do the research obtained the majority of early mobilization well 21 Respondents (67.7%) with healed wounds as many as 20 Respondents (64.5%) Meanwhile, early mobilization with less than 10 respondents (32.3%) with unhealed wounds as many as 11 respondents (35.3%). Based on research results can be concluded that there was a relationship between early post sectio caesarean mobilization against healing surgical scars at KT IV 01.07.03 general hospital in Padangsidimpuan 2020. Where p = 0,000. Expected health worker scan improve professionalism in providing services to patients, especially in give early mobilization after cesarean section.